Investigação do funcionamento cognitivo de pacientes pediátricos diagnosticados com leucemia linfóide aguda - LLA - Gomes, Ediana Rosselly de Oliveira (2011)
The present work investigated the cognitive operation of children diagnosed with acute lymphoblastic leukaemia (ALL), accompanied at pediatric oncologic institutions at the city of Natal/RN. Had participated in this study twenty children, of both sexes, between six and twelve years old, with the ALL diagnostic, who were in treatment (n=10) and out of treatment for at least one year (n=10) and were submitted exclusively to chemotherapy as CNS prophylaxis. The utilized protocol of neuropsychological evaluation covered the following cognitive abilities: intellective capability, attentional and memory systems, and executive functions. Data was analyzed through descriptive and inferential measures, with the support of the Mann-Whitney U Test and T-test, considering the influence of the variables sex, age at diagnostic and the past time since the beginning of the treatment over children s performance. The intellective capability evaluation showed low score to the out-of-treatment groups, female and children under five years old to the diagnostic. In concern of attentional systems, groups showed the expected performance. In a relevant way, in the evaluation of executive functions, were found reduced scores within all groups, especially inside the in-treatment group. Memory evaluation pointed to reduced performance in items concerning to learning evolution and spontaneous evocation after interference to the several groups. It can be concluded, reffer to the occurrence of transitory and permanent impact associated to the intrusion of chemotherapic components during the maturational course of the CNS. It s expected that the present investigation and the development of similar studies enable major comprehension about the mode, extension and repercussion of these damages subsidizing the development of strategies which may minimize them and provide better xxiii life quality to this clinical subgroup